Double NCED isozymes control ABA biosynthesis for ripening and senescent regulation in peach fruits. (March 2021) - Wang, Pengfei; Lu, Siyuan; Zhang, Xueying; Hyden, Brennan; Qin, Lijie; Liu, Lipeng; Bai, Yangyang; Han, Yan; Wen, Zhiliang; Xu, Jizhong; Cao, Hongbo; Chen, Haijiang
Highlights: Double NCED isozymes regulated ABA biosynthesis in peach fruits. PpNCEDs had functional divergence. ABA might promote fruit ripening and senescence through ROS. Abstract: During ripening, peach fruits ( Prunus persica L. Batsch) rapidly progress to the senescent stage, resulting in a brief shelf life. Abscisic acid (ABA) plays an important role in regulating the ripening process, both in climacteric and non-climacteric fruits. A key enzyme for ABA biosynthesis in higher plants is 9- cis -epoxycarotenoid dioxygenase (NCED). In this study, two NCED isozymes, PpNCED1 and PpNCED5, were identified in peach fruits. While both NCED genes had similar transcriptional patterns (up-regulation) at the beginning of peach ripening, PpNCED5 showed a consistently lower expression level than PpNCED1 . During the post-harvest stage, gene expression of PpNCED1 declined, while PpNCED5 expression increased relative to PpNCED1 expression. Considering the dynamic process of ABA accumulation during fruit ripening and senescence in peach, this study indicates that both NCED genes cooperatively control ABA biosynthesis in peach fruits. Moreover, spatio-temporal expression and transcriptional response to hormone and abiotic stress suggested that there is functional divergence between PpNCED1 and PpNCED5 genes in peach. A carotenoid-rich callus system was used to verify the function of PpNCED1 and PpNCED5 . In the transgenic callus system, both PpNCED1 and PpNCED5 isozymes promoted ABA biosynthesis, which likely accelerated cell senescence through activating ROS signals. The results from this study provide evidence supporting an ABA biosynthetic regulation process via the two NCED genes in peach fruit, and suggest a mechanism of ABA-induced fruit ripening and senescence.